Endometrial preparation with stimulated versus artificial cycle: a comparative study on frozen embryo transfer outcomes - Sharma, Sangeeta; Himabindu, Y.; Dondhu, Kiramai; Rakholia, Reha; Sinha, Shweta; Swapnil; Dubey, Ambika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Successful frozen–thawed embryo transfer (FET) depends on adequate endometrial preparation. Stimulated cycles (SC) may provide a more physiological hormonal milieu by supporting corpus luteum function, whereas artificial cycles (AC) offer flexible scheduling but rely entirely on exogenous hormones. Existing evidence comparing these two approaches remains inconsistent. This study aimed to evaluate reproductive outcomes following FET using stimulated versus artificial cycles. Methods: This prospective comparative study included 89 women undergoing their first FET between January 2024 and April 2025. Participants were prepared using either a stimulated cycle (n=31) involving letrozole with low-dose gonadotropins or an artificial cycle (n=58) using estrogen–progesterone replacement. Endometrial thickness was monitored and two good-quality day-3 embryos were transferred after adequate progesterone exposure. Outcomes assessed were positive pregnancy test, clinical pregnancy, ongoing pregnancy at 12 weeks and early pregnancy loss. Statistical analysis was performed using Student’s t-test, Chi-square test or Fisher’s exact test, with p<0.05 considered significant. Results: Baseline characteristics including age, BMI, infertility duration and ovarian reserve were comparable between groups. Pregnancy outcomes were higher in the SC group but did not reach statistical significance: positive pregnancy rate (41.9% vs. 31.0%, p=0.32), clinical pregnancy rate (32.3% vs. 24.1%, p=0.41) and ongoing pregnancy rate (29.0% vs. 19.0%, p=0.27). Early pregnancy loss remained low in both groups (3.2% vs. 5.2%, p=1.00). Conclusions: Stimulated cycles showed a trend toward improved pregnancy outcomes compared with artificial cycles; however, differences were not statistically significant. Both protocols yielded acceptable clinical results, supporting individualized selection of endometrial preparation based on patient characteristics and clinical judgment.